Enantioselective Michael Addition of Cyclohexanone to Nitroolefins Catalyzed by a New Pyrrolidinyl-isosteviol Bifunctional Organocatalyst in Water - Liu, Yu-Xia; Xu, Yuan-Yuan; Li, Shuai; Pan, Zi-Qing; Li, Bing-Xue; Fan, Zhao-Yang (Letters in Organic Chemistry, 2024)
A new pyrrolidinyl-isosteviol bifunctional organocatalyst was synthesized, which was applied to catalyze the asymmetric Michael addition between cyclohexanone and nitroolefins. With 10 mol % of the organocatalyst, the reaction proceeded in water in high yields (up to 99%) with excellent diastereoselectivities (anti/syn up to 98:2) and good enantioselectivities (up to 90% ee). The design of the proline-isosteviol conjugates as organocatalysts was based on the crucial role of proline in the formation of enamine. To sum up, a new pyrrolidinyl-isosteviol bifunctional organocatalyst was synthesized, which could effectively catalyze the C-C formation reaction between a number of nitroolefins and cyclohexanone.
Keywords: asymmetric catalysis